Getting back in the game after humeral head resurfacing - Bülhoff, Matthias; Sowa, Boris; Bruckner, Thomas; Raiss, Patric; Zeifang, Felix (Journal of orthopaedics, 2018)
Background - Aim of this investigation was to analyze whether patients undergoing humeral head resurfacing (HHR) surgery are able to successfully return to their sports and occupation afterwards. - Materials and methods - Fifty patients treated with CUP (HHR) arthroplasty were included. Two groups were built: Patients who have participated in sports less than 5 years prior surgery (Group 1: n=42 (84%)) and patients who have never participated in sports (Group 2: n=8 (16%)). Evaluation was based on a questionnaire asking for types of sports, frequency, time to return to sports and work as well as limitations in work life. - Results - Mean age at the time of surgery was 58.6 (36–84) years in Group 1 and 65 (56–75) years in Group 2. Mean time follow-up was 5.5 years (2.5–12) years. Twenty-seven (64%) patients in Group 1 participated in sports right before surgery. Twenty-one patients (50%) returned to sports after surgery. The returning rate was 78%. Seven (17%) patients in Group 1 stated that the reason they underwent shoulder replacement surgery was to continue to participate in sports. Swimming and skiing were two of the most favorable sports. Two (4%) patients had to change their profession due to surgery. Most of the patients were retired at follow-up. - Conclusion - Most of the active patients undergoing HHR surgery are successfully able to return to their sports activities after surgery. Patients employed were able to return to their occupation after surgery. Many patients were already retired at the time of follow up.
Gesehen am 28.01.2020